The Association between Treatment for Metabolic Disorders and Breast Cancer Characteristics - Hadar Goldvaser; Shulamith Rizel; Daniel Hendler; Victoria Neiman; Daniel Shepshelovich; Tzippy Shochat; Aaron Sulkes; Baruch Brenner; Rinat Yerushalmi (International Journal of Endocrinology)
Purpose. To evaluate the associations between metformin, insulin, statins, and levothyroxine and breast cancer characteristics and outcome. Methods. Retrospective chart review of patients treated in our institute for early estrogen receptor (ER) positive, human epidermal growth factor receptor 2 negative breast cancer, whose tumors were sent to Oncotype DX (ODX) analysis. Patients were grouped according to medications usage during the time of breast cancer diagnosis. Each group was compared to the rest of the study population. Results. The study cohort included 671 patients. Sixty (9.1%) patients were treated with metformin, 9 (1.4%) with insulin, 208 (31.7%) with statins, and 62 (9.4%) with levothyroxine. Patients treated with metformin had more intense ER stain (p=0.032) and a lower ODX recurrence score (RS) (p=0.035). Diagnosis of diabetes mellitus was also associated with lower ODX RS (p=0.014). Insulin usage was associated with a higher rate of angiolymphatic invasion (p=0.041), but lower Ki67% (p=0.017). Levothyroxine usage was associated with different histological subtype distribution (p=0.02). Extended levothyroxine usage was associated with lower ODX RS (p=0.005). Statin usage had no impact on tumor characteristics. Outcome was comparable in the studied subgroups. Conclusions. Common medications for metabolic disorders might be associated with breast cancer characteristics.